A CMOS multichannel 10-Gb - Takauchi, H. (IEEE Journal of solid state circuits)
We describe a CMOS multichannel transceiver that transmits and receives 10 Gb/s per channel over balanced copper media. The transceiver consists of two identical 10-Gb/s modules. Each module operates off a single 1.2-V supply and has a single 5-GHz phase-locked loop to supply a reference clock to two transmitter (Tx) channels and two receiver (Rx) channels. To track the input-signal phase, the Rx channel has a clock recovery unit (CRU), which uses a phase-interpolator-based timing generator and digital loop filter. The CRU can adjust the recovered clock phase with a resolution of 1.56 ps. Two sets of two-channel transceiver units were fabricated in 0.11-μm CMOS on a single test chip. The transceiver unit size was 1.6 mm × 2.6 mm. The Rx sensitivity was 120-mVp-p differential with a 70-ps phase margin for a common-mode voltage ranging from 0.6 to 1.0 V. The evaluated jitter tolerance curve met the OC-192 specification.